Linking Agronomic and Knowledge Barriers to Adoption of Conservation Practices for Nitrogen Management - Khalsa, Sat Darshan S.; Rudnick, Jessica; Lubell, Mark; Sears, Molly; Brown, Patrick H. (Frontiers in Agronomy, 2022)
Agricultural nitrogen (N) use is a major contributor to environmental problems arising from nitrous oxide emissions and N loading to groundwater. Advances in the adoption of conservation practices requires a better understanding of the agronomic context for cropping systems. This paper tests hypotheses about how agronomic and knowledge barriers influence the adoption of conservation practices for N management in orchard agroecosystems. Agronomic barriers are characterized by farm size, irrigation systems and access to water resources, and knowledge barriers are influenced by the availability of information and use of information sources. Our study focuses on the California’s San Joaquin Valley where we collected 879 in-person surveys from fruit and nut growers focused on ten different conservation practices related to fertilizer use, irrigation and soil health. We used logistic regression models to identify parameters influencing adoption and differences in adoption between fruit and nut growers. Our results indicate that overall growers report higher adoption for practices for fertilizer use compared to irrigation and soil health. Growers with larger parcels, microirrigation and more water security had a higher probability of practice adoption. Nut crops are more agronomically intense than fruit crops requiring higher rates of N fertilizer and water use. Nut growers adopted significantly more practices than fruit growers, and also utilized significantly more information sources and experienced significantly fewer practice challenges. Our results collectively support our hypotheses that agronomic and knowledge barriers differ between fruit and nut growers, and help to explain the variance in adoption of conversation practices in orchard agroecosystems. Furthermore, the significant of our work offers a case study for other regions and agroecosystems to address the need for linking agronomic and knowledge barriers to adoption in an effort to promote global climate-smart and regenerative agriculture initiatives.